Effect of Chronic Orofacial Pain for Subjective Sleep - Narita, Noriyuki; Kubo, Hideyuki; Makiyama, Yasuhide; Nishimori, Hideta; Shimosaka, Michiharu; Nishimura, Hitoshi; Wake, Hiroyuki; Okubo, Masakazu; Kamiyama, Hirona; Iida, Takashi; Uchida, Takashi; Komiyama, Osamu; et al. (Japanese Journal of Orofacial Pain, 2016)
Purpose: The aim of this study was to compare the subjective sleep influenced by duration of chronic pain with temporomandibular disorders （TMD）, burning mouth syndrome （BMS） and trigeminal neuralgia（TGN） patients. Methods: Subjects in the Orofacial and Head Pain Clinic, Nihon University Hospital at Matsudo were selected according to the research Diagnostic Criteria for TMD （n＝1838）, International Association for the Study of Pain criteria for BMS （n＝396）, and the International Classification of Headache Disorders for TGN （n＝108）. In each disorder, subjects classified acute stage group （＜ 3 month）, middle stage group （from 3 month to 6 month）, and chronic stage group （＞ 6 month） according to lengthen chronic pain. Difficulty falling asleep （DFS）, arousal during sleep （AS）, and early-morning awakening （EA） scores were evaluated from questionnaire in each group from all disorders. Results: DFS, AS, and EA at chronic stage group in TMD were significantly higher than at acute stage group and middle stage group （p＜0.01）. DFS, and AS at chronic stage group in BMS were significantly higher than at acute stage group and middle stage group （p＜0.05）. There were no significantly differences in DFS, AS, and EA between each group in TGN. Conclusions: Our result suggests that quality of sleep in TMD and BMS patients influenced by their lengthen chronic pain.